Tài liệu học tập kiểm soát nội bộ tổ chức tài chính vi mô
Tài liệu học tập kiểm soát nội bộ tổ chức tài chính vi mô / Nguyễn Hồng Yến chủ biên; Nguyễn Võ Tuyết Trinh,...thành viên .- H. : Lao động , 2018 .- 144tr. ; 21 cm